2020
DOI: 10.3390/app10248949
|View full text |Cite
|
Sign up to set email alerts
|

An Attempt to Reduce the Background Free Radicals in Fingernails for Monitoring Accidental Hand Exposure of Medical Workers

Abstract: While it is recognized that some medical workers could receive significantly higher radiation doses to their hands than the routinely monitored personal doses, accurate retrospective dosimetry of their hand exposure is still challenging. To solve this issue, a combination of electron spin resonance (ESR) measurement and fingernails is worth to be investigated. However, the application of fingernail ESR dosimetry requires establishing an effective protocol to eliminate the background signal (BKG) which changes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The BKS was found to decrease by a factor of 3.2 but was not entirely removed. Similar results were seen by Gonzales et al (2020) in non-irradiated fingernails treated with 0.1 M DTT for 30 min [59]. These results suggest that those o-semiquinone radicals accessible to the reducing treatment were likely reduced to the diamagnetic dihydroquinone.…”
Section: Oxidation-reduction Properties Of Bkssupporting
confidence: 76%
See 1 more Smart Citation
“…The BKS was found to decrease by a factor of 3.2 but was not entirely removed. Similar results were seen by Gonzales et al (2020) in non-irradiated fingernails treated with 0.1 M DTT for 30 min [59]. These results suggest that those o-semiquinone radicals accessible to the reducing treatment were likely reduced to the diamagnetic dihydroquinone.…”
Section: Oxidation-reduction Properties Of Bkssupporting
confidence: 76%
“…The radicals associated with the BKS and RIS 5 may not lend themselves to differences in distribution or localization of the two groups of radicals within the nail, although this remains to be investigated further. It has been suggested that BKS could be reduced through the use of an antioxidant during hand washing prior to starting work within an environment where exposure to radiation may occur as a part of radiological emergency preparedness in occupations such as first responders or medical workers [59]. However, this approach may not be amenable in situations where the radiation exposure has already occurred.…”
Section: Discussionmentioning
confidence: 99%
“…Lastly, under the main topic of dosimetry, the Special Issue includes the study by Gonzales et al [20] which contribute to the development of a practical protocol for fingernail electron spin resonance (ESR) dosimetry useful for the routine monitoring of the extremity exposures of medical workers handling radiation sources. The authors investigate the effects of chemical treatment using dithiothreitol (DTT) on the changes of the ESR spectra in irradiated and unirradiated fingernails after a long storage time.…”
Section: Contributionsmentioning
confidence: 99%
“…Most EPR measurements are performed in the X-band and some aim to detect signals in small amount of samples with the higher-frequency Q-band measurements [3]. Although EPR has a long history, its application to dosimetry is a novel application technique [4]. Attempts have also been made to measure the internal exposure of environmental organisms using radiation-induced signals in the sample [5].…”
Section: Introductionmentioning
confidence: 99%